A phenomenological study of gay male undergraduate college students' experiences at a Jesuit Catholic university - Willette, James M., author; Kuk, Linda, advisor; Anderson, Sharon, committee member; Miller, Lisa, committee member; Scott, Malcolm, committee member (Colorado State University. Libraries, 2016)
The purpose of this interpretative phenomenological study was to understand how male undergraduate students who identify as openly gay experience marginality and mattering at a Jesuit Catholic university. There were 28 Jesuit colleges and universities in the United States as of this writing, each with its own varying approach towards the treatment of gay and lesbian students. Much like the state of the Catholic Church in the era of Pope Francis, many Jesuit colleges and universities struggle with the philosophical contradiction between maintaining a distinctly Catholic identity and creating a campus climate that reflects the Jesuit values of care and social justice. Using Schlossberg’s (1989) theory of marginality and mattering in college environments as the theoretical framework, data were collected from fourteen participants through semi-structured interviews, which took place at a Jesuit Catholic university in the Pacific Northwest region of the United States. Data were then analyzed using interpretative phenomenological analysis, which yielded three cross-case superordinate themes and ten sub-themes. The three cross-case superordinate themes—Identity; Campus Climate, and; The Church and the Institution—described key elements of participants’ experiences as male undergraduate students who identify as openly gay at a Jesuit Catholic university and how these students experienced marginality and mattering on-campus. Each of the three main themes was then used as a lens to explore how participants experienced marginality and mattering.